Syntax of Hungarian Coordination and Ellipsis - Bánréti, Zoltán (Comprehensive Grammar Resources, 2022)
Syntax of Hungarian aims to present a synthesis of the currently available syntactic knowledge of the Hungarian language, rooted in theory but providing highly detailed descriptions, and intended to be of use to researchers, as well as advanced students of language and linguistics. As research in language leads to extensive changes in our understanding and representations of grammar, the Comprehensive Grammar Resources series intends to present the most current understanding of grammar and syntax as completely as possible in a way that will both speak to modern linguists and serve as a resource for the non-specialist. This volume provides a comprehensive overview and description of coordinate structures, the syntactic and semantic types of conjunctions, as well as the types of ellipses in sentences and short dialogues. It discusses multiple conjunctions, coordinated wh-constructions, sluicing, and sentence fragments.